Taxonomy and typification of Hoya meliflua (Apocynaceae, Asclepiadoideae) - Rodda, Michele (Phytotaxa, 2016)
Hoya meliflua, H. treubiana and H. luzonica are typified. A recent neotypification of Hoya meliflua ssp. fraterna is considered invalid, the original type is reinstated and an epitype is designated. Upon examination of the type specimens, H. davaoensis, H. luzonica, H. meliflua ssp. fraterna and H. treubiana are considered conspecific with H. meliflua.